REPRESENTASI KEBOCORAN DATA DALAM IKLAN IPHONE DATA AUCTION (ANALISIS SEMIOTIKA JOHN FISKE) - Dennisa Nayla Rizkia (2023)
In the current era of digital advancement 4.0, the proliferation of information technology has led to a concerning increase in personal data breaches by irresponsible parties. This global phenomenon has affected many organizations, including tech giant Apple Inc., which took measures to restore its reputation. Apple Inc. then released an online advertisement called "Data Auction," which showcases its renewed security system and commitment to safeguarding its users' personal data. Employing John Fiske's semiotics theory, this research seeks to analyze the advertisement's depiction of data breaches across reality, representation, and ideology using descriptive and qualitative research methods. The results indicate that the Data Auction advertisement employs various representations of data breaches to create a distinctive atmosphere, with underlying authoritarian, capitalist, and liberal ideologies.